Manusia dalam Al-Qur’an Menurut Perspektif Filsafat Manusia - Seha, Sampo (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2017)
This article deals with the concept of human being on Quran perspective and philosophy field. Quran, as the main source of Islam, has clearly discussed the creation of human being as stated in different surah of Quran. It was found that the creation oh human being refer to God’s intention. In other words, this paper employes belief approach to see human being in terms of creation, especially when looking at the first human living in the world. Adam was believed as the first father of all human being while Hawa was the first mother af all human species. Quran, futhermore, continue presenting that Adam was generated from different kinds of soils. On the other hand, human being, in accordance with philosophy perspective, is regarded from various perspective. The most familiar one is the theory of Darwain in terms of evolution. This theory provides an understanding that human being was generated from ape. All in all, the author tried to counter this theory through presenting Quranic theories as well as proving that creation of human being can be seen logically.